1983
DOI: 10.1159/000128354
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Energy Restoration of Ischemic Damage by Administration of Phosphoenolpyruvate during Reperfusion

Abstract: The myocardial energy restoration of ischemic damage by administration of phosphoenolpyruvate during reperfusion was investigated in a paracorporeal heart model modified in the rat. Excised hearts were subjected to 15 min of complete global ischemia at 37 °C before pulsatile blood reperfusion for 30 min. One group (n = 7) was supplemented with 67 µmol of phosphoenolpyruvate and 0.67 µmol of adenosine triphosphate dissolved in 10 ml of saline and another with plain saline (nonsupplemented) during reperfusion. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 14 publications
3
16
0
Order By: Relevance
“…The results of this in vitro study confirm previous in vivo results showing a protective effect afforded by PEP in various animal disease models, 1,[3][4][5][6] and these effects may be exerted, at least in part, through the cytoprotective and antioxidant effects of PEP. Combined with the in vivo and in vitro results, we suggest that administration of PEP may have therapeutic value in treating diseases whose etiology involves ROS.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of this in vitro study confirm previous in vivo results showing a protective effect afforded by PEP in various animal disease models, 1,[3][4][5][6] and these effects may be exerted, at least in part, through the cytoprotective and antioxidant effects of PEP. Combined with the in vivo and in vitro results, we suggest that administration of PEP may have therapeutic value in treating diseases whose etiology involves ROS.…”
Section: Discussionsupporting
confidence: 88%
“…PEP can penetrate the cell membrane and transfer its highenergy phosphate group to adenosine diphosphate, aiding the replenishment of intracellular ATP. 1,2) It has been reported that PEP improved post-ischemic energy status in the heart, 3) skeletal muscle, 4) and liver 1) in rats. Hojo et al 5) demonstrated that transplanted kidney function and graft survival were improved by PEP in experimental kidney transplantation in a canine model.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…PEP contains a high-energy phosphate group and efficiently supplies energy to ischemic/ reperfused organs in vivo and in situ 15,[17][18][19][20] Our current results suggest that the in vitro protective effects of PEP against cellular injury induced by the glycolysis inhibitor, 2-DG, used as an in vitro model of ischemic organ injury due to energy metabolism dysfunction, 21) may be due to the fact that PEP replenishes cellular ATP and acts as a cytoprotective agent against energy metabolism dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…PEP can penetrate the cell membrane and transfer its high-energy phosphate group to adenosine 5 -diphosphate (ADP) to replenish intracellular ATP levels. 15,16) It has been reported that PEP improves the energy status of the heart 17,18) and skeletal muscle 19) after ischemia, and of the liver after ischemia-reperfusion. 15) Hojo et al 20) demonstrated that the survival of transplanted kidney grafts was improved by Euro-Collins solution containing 10 mM PEP in a canine experimental kidney transplantation model.…”
Section: Introductionmentioning
confidence: 99%